Noninvasive assessment of liver fibrosis in Nonalcoholic Fatty Liver Disease in Nepal - Sah, Manoj Kumar; Basnet, Bhupenndra Kumar; Poudyal, Nandu Silwal; Karki, Niyanta; Shrestha, Roshan (Journal of Advances in Internal Medicine, 2020)
Background and Aims: Nonalcoholic Fatty Liver Disease (NAFLD) progresses to liver fibrosis and ultimately cirrhosis and its complications. Grading of liver fibrosis 2D SWE (Shear Wave Elastography) is a noninvasive study of liver fibrosis and stiffness. We compared different fibrosis scores (NAFLD fibrosis score, FIB 4 score, APRI score) and ultra-sonogram identified fatty liver with 2d shear wave elastography score.Methods: A hospital based prospective observational study was conducted from May 2019 for ten months period in the Gastroenterology and Liver Unit, NAMS, Nepal. Seventy patients with known fatty liver and its severity were identified by Ultrasonogram criteria were enrolled, who met the exclusion criteria. All patients underwent 2D shear wave elastography. Patients were evaluated for effects of obesity, diabetes mellitus, thyroid related disease and dyslipidemias on NAFLD. Tests were done to calculate diﬀerent fibrosis scores (NAFLD Fibrosis, FIB4, APRI, AST/ALT ratio) and compared with 2d shear wave score.Results: Baseline Characteristics among 70 patients 39(55.7%) were male and 31(44.3%) were female with mean age of the patients 44.3 years. Most of the patients were overweight with mean BMI of 28.2, kg/m2among them 51(72.9%) patients were more than 25.kg/m2Most of the patients 41.4% had diabetes mellitus, 77.1% had hypertension, 30% had hypothyroidism and were 25.9% had metabolic syndrome. Majority of patients on ultrasound gradings were mild 64.28%, 25.72% were moderate and only 10 % were in severe groups. In comparison ultra-sonogram with 2 d shear wave elastography, mild grade mean fibrosis 7.07 kpa, for moderate grade mean fibrosis 8.22 kpa and for severe grade mean fibrosis was 18.16 kpa.Conclusion: In patients with NAFLD, measurement of liver stiffness by 2d shear wave elastography has positively correlated with FIB-4 score and non-inferior to NAFLD fibrosis score. The mean value of elastography increases significantly with the severity of steatosis on ultrasonography.